An EXAFS Approach to the Study of Polyoxometalate–Protein Interactions: The Case of Decavanadate–Actin - Marques, M. Paula M. (2017)
EXAFS and XANES experiments were used to assess decavanadate interplay with actin, in both the globular and polymerized forms, under different conditions of pH, temperature, ionic strength, and presence of ATP. This approach allowed us to simultaneously probe, for the first time, all vanadium species present in the system. It was established that decavanadate interacts with G-actin, triggering a protein conformational reorientation that induces oxidation of the cysteine core residues and oxidovanadium (VIV) formation. The local environment of vanadium's absorbing center in the [decavanadate-protein] adducts was determined, a V-SCys coordination having been verified experimentally. The variations induced in decavanadate's EXAFS profile by the presence of actin were found to be almost totally reversed by the addition of ATP, which constitutes a solid proof of decavanadate interaction with the protein at its ATP binding site. Additionally, a weak decavanadate interplay with F-actin was suggested to take place, through a mechanism different from that inferred for globular actin. These findings have important consequences for the understanding, at a molecular level, of the significant biological activities of decavanadate and similar polyoxometalates, aiming at potential pharmacological applications.